Electrode catalyst and fuel cell system
By covering the carbon film of nitrogen and micropores on the surface of the fuel cell electrocatalyst and using a gas supply system without humidity under low humidity conditions, the problem of poor performance of fuel cells under low humidity conditions is solved, and efficient and durable power generation is achieved.
Patent Information
- Application Number
- JP2023154000
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-04-02
AI Technical Summary
The prior art is difficult to achieve high-performance fuel cell systems under low humidity conditions, especially in the absence of fluoride treatment.
An electrocatalyst is used with a carbon film covered with nitrogen and micropores on the surface, used for the anode electrode layer of the fuel cell, and equipped with a gas supply system without humidification, with a relative humidity of 30% RH or below.
By reducing the contact area between the catalyst particles and the ionic plasma membrane, the adsorption of acid groups in the ionic plasma membrane is inhibited, the activity and durability of the catalyst is improved, and efficient power generation is maintained under low humidity conditions.
Smart Images

Figure 2025045934000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode catalyst and a fuel cell system, and more particularly to an electrode catalyst that exhibits high performance under low humidification conditions, and a fuel cell system equipped with such an electrode catalyst. [Background technology]
[0002] A polymer electrolyte fuel cell is equipped with a membrane electrode assembly (MEA) in which electrodes containing a catalyst are bonded to both sides of an electrolyte membrane. Current collectors (separators) equipped with gas flow paths are further arranged on both sides of the MEA. A polymer electrolyte fuel cell usually has a structure (fuel cell stack) in which multiple unit cells, each of which is made of an MEA and a current collector, are stacked together.
[0003] Fuel cell electrodes are usually made of a laminate of a catalyst layer arranged on the electrolyte membrane side and a diffusion layer arranged on the gas flow path side. The catalyst layer generally consists of a mixture of an electrode catalyst in which catalyst particles (active species) such as platinum or platinum alloy are supported on the surface of a carrier, and a catalyst layer ionomer. Electrode reactions mainly occur on the surface of the catalyst particles. For this reason, efforts are being made to make the catalyst particles as fine as possible and reduce the amount of platinum used per unit area of the electrode. However, in the operating environment of a fuel cell accompanied by potential fluctuations, the finer the catalyst particles, the more likely they are to dissolve, coarsen due to aggregation, and / or become detached from the support, resulting in a gradual decrease in the activity of the catalyst layer.
[0004] In order to solve this problem, various proposals have been made in the past. For example, Non-Patent Document 1 states: (a) Irregular fcc-PtFe nanoparticles are supported on the surface of carbon particles, (b) The nanoparticle surface is coated with polydopamine by treating it with an aqueous solution of dopamine hydrochloride. (c) The fcc-PtFe nanoparticles (fcc-PtFe / C) supported on carbon particles and coated with dopamine are heat-treated at 700°C to obtain an ordered fct-PtFe nanoparticle catalyst (fct-Pt / Fe / C) coated with N-doped carbon. A method for producing a PtFe nanoparticle catalyst is disclosed.
[0005] The same document states: (A) When PtFe / C without dopamine coating is heat-treated, the size of the nanoparticles increases to several tens of nanometers, whereas when PtFe / C coated with dopamine is heat-treated, the size of the nanoparticles remains almost the same as before the heat treatment (6.5 nm). (B) The N-doped carbon shell-coated fct-PtFe / C catalyst exhibits 11.4 times higher mass activity and 10.5 times higher specific activity than the commercial Pt / C catalyst; and (C) Covering Pt / C with an N-doped carbon shell has negligible effect on activity. is stated.
[0006] Patent Document 1 describes a catalyst comprising catalyst particles and a carbon film that covers the surface of the catalyst particles, the content of chloride ions per unit surface area of the catalyst particles being 12.5 μg / m 2 An electrocatalyst is disclosed that is less than The same document states: (a) When the surface of a catalyst particle is coated with a film derived from an organic substance and then heat-treated, an electrode catalyst in which the surface of the catalyst particle is coated with a carbon film is obtained; (b) When the obtained electrocatalyst is washed, the chloride ions adsorbed on the surface of the catalyst particles are released, improving the initial activity compared to that of an electrocatalyst that has not been washed; and (c) The carbon film suppresses dissolution, aggregation, and / or detachment of catalyst particles and suppresses ionomer poisoning of catalyst particles, thereby improving initial activity and durability. is stated.
[0007] Patent Document 2 discloses an electrode catalyst that includes catalyst particles and a nitrogen-containing carbon membrane that covers the surfaces of the catalyst particles, the nitrogen-containing carbon membrane including micropores. The same document states: (A) When the surface of a catalyst particle is coated with polymelamine and polydopamine, and the polymelamine and polydopamine are thermally decomposed, an electrode catalyst in which the surface of the catalyst particle is coated with a nitrogen-containing carbon film containing micropores is obtained; and (B) The electrode catalyst thus obtained may have improved initial activity and durability compared to an electrode catalyst coated with a polydopamine-derived carbon film. is stated.
[0008] Patent Document 3 discloses a catalyst for polymer electrolyte fuel cells obtained by mixing a catalytic metal-supported carbon material in which a catalytic metal component is supported on a support made of a porous carbon material, with a catalytic metal-unsupported carbon material made of a dendritic graphitic carbon material. The document describes that when a catalyst layer is formed using such a catalyst, a water-repellent catalytic metal-unsupported carbon material is placed near a hydrophilic catalytic metal-supported carbon material, so that water vapor generated in the catalytic metal-supported carbon material is quickly discharged outside the catalyst layer via the catalytic metal-unsupported carbon material, thereby suppressing flooding.
[0009] As-synthesized PtFe alloy nanoparticles have an irregular face-centered cubic (fcc) structure and low catalytic activity. When they are heat-treated at 700°C, they change to a regular face-centered tetragonal (fct) structure, improving the area-specific activity. However, the heat treatment process causes the nanoparticles to coarsen, resulting in a significant decrease in mass activity.
[0010] In contrast, Non-Patent Document 1 describes that coating the surface of PtFe alloy nanoparticles with dopamine and heat-treating them at 700° C. suppresses the increase in particle size of the nanoparticles. It explains that this is because the thin carbon film (a thermal decomposition product of dopamine) that covers the nanoparticle surface suppresses the aggregation of nanoparticles that occurs during the heat treatment process. In addition, Non-Patent Document 1 describes that the fct-PtFe / C catalyst that has been subjected to such treatment has improved area activity, mass activity, and durability compared to a pure Pt / C catalyst or an irregular fcc-PtFe / C catalyst. It is explained that the improved durability is due to the carbon film covering the Pt surface suppressing the dissolution, aggregation, and detachment of Pt that occurs during the durability test.
[0011] However, the effect of the carbon film itself, which is produced by dopamine modification and heat treatment, on the performance of the catalyst has not been fully elucidated. In fact, Non-Patent Document 1 reports that even when a pure Pt / C catalyst was coated with dopamine and heat-treated at 700°C, the initial performance did not improve. The reason for this is thought to be that impurities mixed into the catalyst during the modification process had a negative effect on the performance.
[0012] On the other hand, Patent Document 1 describes that if the surface of a pure Pt / C catalyst is coated with a dopamine-derived carbon film and then the electrode catalyst is washed, the initial activity and durability of the electrode catalyst are improved. However, in order to further improve the performance of fuel cells, it is desirable to further improve the initial activity and durability of the electrode catalyst.
[0013] In addition, Patent Document 2 describes that low-load activity and durability are improved by covering the surface of catalyst particles with a nitrogen-containing carbon membrane containing micropores. However, in order to further improve the performance of fuel cells, it is desirable to further improve activity at medium and high loads.
[0014] Patent Document 3 also describes that in order to support the catalytic metal component not only on the surface of the support but also inside the pores, the support needs to have many mesopores with a diameter of 4 nm or more and less than 10 nm. However, in order to support the catalytic particles inside the mesopores, the size of the catalytic particles and the manufacturing process may be limited. In addition, protons cannot reach the catalytic particles supported deep inside the mesopores, so they cannot be used for electrode reactions. Therefore, the size of the primary particle diameter of the support may be limited.
[0015] Furthermore, Patent Document 2 shows the effect of improving performance under high humidification conditions, but does not mention performance under low humidification conditions. When the operating temperature is increased in order to further increase the output of the polymer electrolyte fuel cell, the low humidification conditions are reached. Alternatively, when the cathode gas and / or the anode gas is not humidified in order to reduce the auxiliary power, the low humidification conditions are reached. In order to obtain high output in a fuel cell system with a high operating temperature or a fuel cell system without a humidifier, it is necessary to improve performance under low humidification conditions. However, there have been no examples of electrode catalysts that show high performance under low humidification conditions proposed in the past. [Prior art documents] [Patent documents]
[0016] [Patent Document 1] JP 2020-136109 A [Patent Document 2] JP 2022-142887 A [Patent Document 3] Patent No. 6496531 [Non-patent literature]
[0017] [Non-Patent Document 1] DY Chung, et al., J. Am. Chem. Soc., 2015, 137, 15478-15485 Summary of the Invention [Problem to be solved by the invention]
[0018] An object of the present invention is to provide an electrode catalyst that exhibits high performance under low humidification conditions. Furthermore, another object of the present invention is to provide a fuel cell system equipped with such an electrode catalyst. [Means for solving the problem]
[0019] In order to solve the above problems, the electrode catalyst according to the present invention has the following configuration. (1) The electrode catalyst is Catalyst particles; A carbon film that covers the surface of the catalyst particle; Equipped with The carbon membrane contains nitrogen and micropores. (2) The electrode catalyst is A cathode catalyst layer of a polymer electrolyte fuel cell to which unhumidified cathode gas A or cathode gas B adjusted to have a relative humidity of 30% RH or less is supplied, and / or An anode catalyst layer of the solid polymer electrolyte fuel cell to which unhumidified anode gas A or anode gas B adjusted to have a relative humidity of 30% RH or less is supplied. It is used in.
[0020] The fuel cell system according to the present invention comprises: A polymer electrolyte fuel cell having a catalyst layer containing the electrode catalyst according to the present invention; a gas supply device for supplying non-humidified gas A or gas B adjusted to have a relative humidity of 30% RH or less to the catalyst layer; It is equipped with: Effect of the Invention
[0021] The surfaces of the catalyst particles are coated with polymelamine and polydopamine, and the polymelamine and polydopamine are thermally decomposed to obtain an electrode catalyst in which the surfaces of the catalyst particles are coated with nitrogen and a carbon film containing micropores. When catalyst particles are covered with such a carbon film, the contact area between the catalyst particles and the ionomer is reduced. As a result, ionomer poisoning (a phenomenon in which acid groups in the ionomer are adsorbed onto the catalyst particle surface and reduce active sites) is suppressed, and catalyst activity is improved. In addition, by covering the catalyst particles with a carbon film, elution of the catalyst particles is suppressed, improving durability.
[0022] Furthermore, when the surface of the catalyst particle is covered with a nitrogen-containing carbon film, the surface of the catalyst particle becomes hydrophilic, which improves the proton conductivity on the surface of the catalyst particle and results in high power generation performance even under low humidity conditions. [Brief description of the drawings]
[0023] [Figure 1] 1 shows the total specific surface area, micropore specific surface area, and external surface area of the electrode catalysts obtained in Examples 1.1 to 1.5 and Comparative Example 1. [Diagram 2] 1 shows the total specific surface area, micropore specific surface area, and external surface area of the electrode catalysts obtained in Examples 2.1 to 2.3 and Comparative Example 2. [Diagram 3] 1 shows the cumulative pore volume and micropore volume of the electrode catalysts obtained in Examples 1.1 to 1.5 and Comparative Example 1. [Figure 4] 1 shows the cumulative pore volume and micropore volume of the electrode catalysts obtained in Examples 2.1 to 2.3 and Comparative Example 2.
[0024] [Diagram 5] 1 shows water vapor adsorption isotherms of the electrode catalysts obtained in Example 1.5 and Comparative Example 1. [Figure 6] 2 shows water vapor adsorption isotherms of the electrode catalysts obtained in Example 2.3 and Comparative Example 2. [Figure 7] FIG. 1 is a graph showing the relationship between the modification layer ratio and the hydrophilicity / hydrophobicity degree of an electrode catalyst containing catalyst A or catalyst B. [Figure 8] 4 shows IV curves of the membrane electrode assemblies obtained in Example 1.3 and Comparative Example 1 at initial stage and after durability test.
[0025] [Figure 9] 4 shows IV curves of the membrane electrode assemblies obtained in Example 2.2 and Comparative Example 2, initially and after a durability test. [Figure 10] FIG. 1 is a graph showing the relationship between the nitrogen content and mass activity of an electrode catalyst containing catalyst A. [Figure 11] FIG. 13 is a graph showing the relationship between the nitrogen content and mass activity of an electrode catalyst containing catalyst B. [Figure 12]FIG. 1 is a graph showing the relationship between the nitrogen content and the mass activity retention rate of an electrode catalyst including catalyst A. [Figure 13] FIG. 13 is a graph showing the relationship between the nitrogen content and the mass activity retention rate of an electrode catalyst containing catalyst B.
[0026] [Figure 14] FIG. 1 is a graph showing the relationship between the nitrogen content and high load performance of an electrode catalyst including catalyst A. [Figure 15] FIG. 13 is a graph showing the relationship between the nitrogen content and high load performance of an electrode catalyst containing catalyst B. [Figure 16] FIG. 1 is a graph showing the relationship between the nitrogen content of an electrode catalyst containing catalyst A and the high load performance maintenance rate. [Figure 17] FIG. 13 is a graph showing the relationship between the nitrogen content of an electrode catalyst containing catalyst B and the high load performance maintenance rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] [Configuration 1] An electrode catalyst comprising: (1) The electrode catalyst is Catalyst particles; A carbon film that covers the surface of the catalyst particle; Equipped with The carbon membrane contains nitrogen and micropores. (2) The electrode catalyst is A cathode catalyst layer of a polymer electrolyte fuel cell to which unhumidified cathode gas A or cathode gas B adjusted to have a relative humidity of 30% RH or less is supplied, and / or An anode catalyst layer of the solid polymer electrolyte fuel cell to which unhumidified anode gas A or anode gas B adjusted to have a relative humidity of 30% RH or less is supplied. It is used in.
[0028] [Configuration 2] 2. The electrode catalyst according to claim 1, further comprising a carbon support that supports the catalyst particles.
[0029] [Configuration 3] The carbon support has a specific surface area of 100 m 2 / g or more 1000m 2 / g or less of the electrode catalyst according to aspect 2.
[0030] [Configuration 4] 4. The electrode catalyst according to any one of configurations 1 to 3, wherein the nitrogen content in the electrode catalyst is 0.1 mass % or more and 15.0 mass % or less. Here, the "nitrogen content in the electrode catalyst" refers to the ratio of the mass of nitrogen contained in the carbon film to the total mass of the electrode catalyst.
[0031] [Configuration 5] 5. The electrode catalyst according to any one of configurations 1 to 4, wherein the modification layer ratio is 1.0 mass % or more and 50.0 mass % or less. Here, the "modification layer ratio" refers to the ratio of the mass of the carbon film to the total mass of the electrode catalyst.
[0032] [Configuration 6] 6. The electrode catalyst according to any one of configurations 1 to 5, wherein the carbon film has a thickness of 0.2 nm or more and 20 nm or less.
[0033] [Configuration 7] 7. The electrode catalyst according to any one of configurations 1 to 6, wherein the carbon membrane has a volume of the micropores of 0.001 cc / g or more and 0.3 cc / g or less.
[0034] [Configuration 8] The carbon membrane has a micropore specific surface area of 10 m 2 / g or more 500m 2 / g or less.
[0035] [Configuration 9] 9. The electrode catalyst according to any one of aspects 1 to 8, wherein the catalyst particles are made of Pt or a Pt alloy.
[0036] [Configuration 10] A solid polymer electrolyte fuel cell having a catalyst layer containing the electrode catalyst according to any one of configurations 1 to 9; a gas supply device for supplying unhumidified gas A or gas B adjusted to have a relative humidity of 30% RH or less to the catalyst layer; A fuel cell system comprising:
[0037] An embodiment of the present invention will be described in detail below. [1. Electrocatalyst] The electrode catalyst according to the present invention is Catalyst particles; A carbon film that covers the surface of the catalyst particle; Equipped with The carbon membrane contains nitrogen and micropores.
[0038] [1.1. Catalyst particles] [1.1.1. Composition] In the present invention, the material of the catalyst particles is not particularly limited. (a) Precious metals (Pt, Au, Ag, Pd, Rh, Ir, Ru, Os), (b) An alloy containing two or more precious metal elements; (c) Alloys containing one or more precious metal elements and one or more base metal elements (e.g., Fe, Co, Ni, Cr, V, Ti, etc.); etc.
[0039] Among these, the catalyst particles are preferably made of Pt or a Pt alloy, since they have high activity in the electrode reaction of the fuel cell. Examples of Pt alloys include Pt-Fe alloys, Pt-Co alloys, Pt-Ni alloys, Pt-Pd alloys, Pt-Cr alloys, Pt-V alloys, Pt-Ti alloys, Pt-Ru alloys, and Pt-Ir alloys.
[0040] [1.1.2. Particle size] The particle size of the catalyst particles is not particularly limited, and the most suitable particle size can be selected according to the purpose. In general, if the particle size of the catalyst particles is too small, the catalyst particles tend to dissolve. Therefore, the particle size of the catalyst particles is preferably 1 nm or more. On the other hand, if the particle size of the catalyst particles is too large, the mass activity decreases. Therefore, the particle size of the catalyst particles is preferably 20 nm or less. The particle size of the catalyst particles is preferably 10 nm or less, and more preferably 5 nm or less.
[0041] [1.2. Carrier] [1.2.1. Materials] The catalyst particles may be used as they are for various applications, or may be used in a state where they are supported on the surface of a carrier. When the catalyst particles are supported on the surface of a carrier, the fine catalyst particles can be stably dispersed, and therefore the amount of catalyst used can be reduced. The material of the support is not particularly limited, but a carbon support is preferable, for example, carbon black, carbon nanotubes, carbon nanohorns, activated carbon, natural graphite, mesocarbon microbeads, glassy carbon powder, etc.
[0042] [1.2.2. Catalyst loading] When the catalyst particles are supported on the surface of the carrier, the amount of catalyst supported is not particularly limited, and the optimal amount can be selected according to the purpose. In general, if the amount of catalyst supported is too small, sufficient activity cannot be obtained. On the other hand, even if the amount of catalyst supported is more than necessary, there is no difference in effect and there is no practical benefit. For example, when catalyst particles made of Pt or a Pt alloy are supported on the surface of a carbon support, the amount of the supported catalyst is preferably 5 mass % to 70 mass %.
[0043] [1.2.3. Specific surface area] The specific surface area of the support is not particularly limited, and an optimal specific surface area can be selected depending on the purpose. For example, when the support is a carbon support, the larger the specific surface area of the carbon support, the easier it is to support catalyst particles in a highly dispersed manner. To obtain such an effect, the specific surface area of the carbon support should be 30 m 2 / g or more. More preferably, the specific surface area is 100 m 2 / g or more, 200m 2 / g or more, or 300m 2 / g or more. On the other hand, even if the specific surface area of the carbon support is made larger than necessary, there is no difference in the effect and there is no practical benefit. Therefore, the specific surface area of the carbon support is set to 1000 m 2 / g or less. More preferably, the specific surface area is 900 m 2 / g or less, or 800m 2 / g or less.
[0044] [1.3. Carbon film] [1.3.1. Composition] The surface of the catalyst particle is coated with a carbon film. In the present invention, the term "carbon film" refers to a film that contains carbon as a main component and contains nitrogen and micropores. The method for producing the carbon film is not particularly limited, but the carbon film is preferably a film obtained by coating the surface of the catalyst particle with a film containing polymelamine and polydopamine and pyrolyzing the film.
[0045] When a coating containing only polydopamine is pyrolyzed, a dense carbon film consisting essentially of carbon is obtained. On the other hand, when a coating containing polymelamine and polydopamine is pyrolyzed, a carbon film containing micropores and having a higher nitrogen content than a carbon film derived from polydopamine is obtained. The nitrogen contained in the carbon film is mainly derived from polymelamine. The amount of nitrogen contained in the carbon film (= the mass ratio of nitrogen contained in the carbon film to the total mass of the carbon film) is usually 0.1 mass% to 35 mass%, depending on the production method.
[0046] The carbon film is (a) A catalyst particle is coated with a film made of a mixture of polymelamine and polydopamine, and the film is then thermally decomposed (simultaneous modification method), or (b) A catalyst particle surface is coated with polymelamine, and then the catalyst particle surface is coated with polydopamine, and the laminated film of polymelamine and polydopamine is then thermally decomposed (sequential modification method). Either of the above may be used. In particular, the carbon membrane obtained by the sequential modification method exhibits higher properties than the carbon membrane obtained by the simultaneous modification method.
[0047] 1.3.2. Micropore volume "Micropore" refers to a pore with a diameter of 2 nm or less. The "micropore volume" refers to a value obtained by measuring the nitrogen adsorption amount of an electrode catalyst and analyzing the result by the t-plot method using solid carbon as the reference isotherm.
[0048] As described above, when polydopamine is pyrolyzed in the presence of polymelamine, a carbon membrane with micropores is obtained. If the volume of the micropores is too small, the mass transfer to the catalyst particle surface is hindered, and the initial activity may decrease. Therefore, the volume of the micropores is preferably 0.001 cc / g or more. On the other hand, if the volume of the micropores is excessive, dissolution, aggregation and / or detachment of the catalyst particles, or ionomer poisoning of the catalyst particles may occur, and therefore the volume of the micropores is preferably 0.3 cc / g or less.
[0049] [1.3.3. Micropore specific surface area] The "micropore specific surface area" refers to the surface area of the micropores per mass of the electrode catalyst. The micropore specific surface area can be obtained by measuring the amount of nitrogen adsorption on the electrode catalyst and analyzing it by the t-plot method.
[0050] If the micropore specific surface area is too small, the transfer of materials to the catalyst particle surface may be hindered, and the initial activity may decrease. Therefore, the micropore specific surface area should be less than 10 m 2 / g or more. The micropore specific surface area is more preferably 20 m 2 / g or more, or 30m 2 / g or more. On the other hand, if the micropore specific surface area is too large, dissolution, aggregation, and / or detachment of the catalyst particles, or ionomer poisoning of the catalyst particles may occur. Therefore, the micropore specific surface area is set to be within 500 m 2 / g or less. The micropore specific surface area is more preferably 400 m 2 / g or less, 300m 2 / g or less, or 200m 2 / g or less.
[0051] Thickness The thickness of the carbon film affects the stability and activity of the catalyst particles. If the carbon film is too thin, the catalyst particles are likely to dissolve, aggregate, and / or detach. In addition, when such an electrode catalyst is applied to a fuel cell electrode, if the carbon film is too thin, the catalyst particles are likely to be poisoned by the catalyst layer ionomer. Therefore, the thickness of the carbon film is preferably 0.2 nm or more. The thickness of the carbon film is preferably 0.5 nm or more, 1.0 nm or more, 2.0 nm or more, 3.0 nm or more, 3.5 nm or more, or 4.0 nm or more.
[0052] On the other hand, if the carbon membrane is too thick, the transport resistance of the reactants increases, and activity may decrease. Therefore, the thickness of the carbon membrane is preferably 20.0 nm or less. The thickness of the carbon membrane is preferably 15.0 nm or less, 10.0 nm or less, 9.5 nm or less, 9.0 nm or less, 8.5 nm or less, 8.0 nm or less, 7.5 nm or less, or 7.0 nm or less.
[0053] [1.4. Characteristics] [1.4.1. Nitrogen content] The "nitrogen content in the electrode catalyst (hereinafter also simply referred to as "nitrogen content")" refers to the ratio of the mass of nitrogen contained in the carbon film to the total mass of the electrode catalyst.
[0054] The nitrogen in the carbon film acts to improve the hydrophilicity of the carbon film. When the surface of a catalyst particle is covered with a hydrophilic carbon film, water is easily adsorbed on the carbon film surface. Therefore, protons are easily supplied to the catalyst particle surface even under low humidity conditions. Furthermore, when the surface of the catalyst particles is coated with such a carbon film, the mass activity retention rate is also improved. This is thought to be because the catalyst particles become more easily coated with a carbon film as the nitrogen content increases, and the carbon film suppresses the movement and aggregation, or dissolution and reprecipitation, of the catalyst particles. In order to obtain such an effect, the nitrogen content is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, 0.3 mass% or more, 0.5 mass% or more, or 1.0 mass% or more.
[0055] On the other hand, if the nitrogen content is excessive, the mass activity of the catalyst particles may decrease. This is thought to be because the carbon film becomes thicker with an increase in the nitrogen content, resulting in a decrease in the catalyst utilization rate or an increase in the transport resistance of the reactants. Therefore, the nitrogen content is preferably 15.0 mass% or less. The nitrogen content is more preferably 10.0 mass% or less, 8.0 mass% or less, or 7.0 mass% or less.
[0056] [1.4.2. Modification layer ratio] The "modification layer ratio" refers to the ratio of the mass of the carbon film to the total mass of the electrode catalyst.
[0057] The carbon membrane according to the present invention contains an appropriate amount of micropores, and therefore can suppress catalyst poisoning and dissolution of catalyst particles without impeding mass transfer to the catalyst particle surface. In addition, the carbon membrane according to the present invention contains an appropriate amount of nitrogen, and therefore can increase the hydrophilicity of the catalyst particle surface. Therefore, when the surface of the catalyst particle is covered with such a carbon membrane, the performance under low humidification conditions is improved. In order to obtain such an effect, the modification layer ratio is preferably 1.0 mass% or more. The modification layer ratio is more preferably 2.0 mass% or more, 3.0 mass% or more, 4.0 mass% or more, or 5.0 mass% or more.
[0058] On the other hand, if the modification layer ratio is excessive, the catalyst utilization rate may decrease or the transport resistance of the reactants may increase. Therefore, the modification layer ratio is preferably 50.0 mass% or less. The modification layer ratio is more preferably 45.0 mass% or less, 40.0 mass% or less, 35.0 mass% or less, or 30.0 mass% or less.
[0059] [1.5. Purpose] In the electrode catalyst according to the present invention, the surface of the catalyst particle is covered with a carbon film containing nitrogen and micropores, and therefore the hydrophilicity of the catalyst particle surface can be increased without impeding the transfer of substances to the catalyst particle surface, and therefore the electrode catalyst according to the present invention exhibits high performance under low humidity conditions (particularly under conditions where the relative humidity is 30% RH or less).
[0060] The electrode catalyst according to the present invention is A cathode catalyst layer of a polymer electrolyte fuel cell to which unhumidified cathode gas A or cathode gas B adjusted to have a relative humidity of 30% RH or less is supplied, and / or An anode catalyst layer of the solid polymer electrolyte fuel cell to which unhumidified anode gas A or anode gas B adjusted to have a relative humidity of 30% RH or less is supplied. It is preferable to use it for.
[0061] Here, "supplying unhumidified gas A" means supplying gas A from a gas supply source to the fuel cell as is, without using a humidifier. "Supplying gas B with a relative humidity adjusted to 30% RH or less" means using a humidifier or condenser to adjust the relative humidity of gas A supplied from a gas supply source to 30% RH or less, and supplying the humidity-adjusted gas B to the fuel cell. In the case of a fuel cell system that does not have a humidifier, the inside of the fuel cell is likely to be in a low humidity environment, and therefore the electrode catalyst according to the present invention is particularly suitable as an electrode catalyst for a polymer electrolyte fuel cell that is mounted in a fuel cell system that does not have a humidifier.
[0062] [2. Fuel Cell Systems] The fuel cell system according to the present invention comprises: A polymer electrolyte fuel cell having a catalyst layer containing the electrode catalyst according to the present invention; a gas supply device for supplying non-humidified gas A or gas B adjusted to have a relative humidity of 30% RH or less to the catalyst layer; It is equipped with:
[0063] [2.1. Polymer electrolyte fuel cell] A polymer electrolyte fuel cell generally comprises a membrane electrode assembly in which catalyst layers (cathode catalyst layer, anode catalyst layer) are bonded to both sides of an electrolyte membrane. The catalyst layer generally comprises an electrode catalyst and a catalyst layer ionomer. A gas diffusion layer is usually disposed on the outer side of the catalyst layer. Furthermore, a separator having a gas flow path is usually disposed on the outer side of the gas diffusion layer.
[0064] In the present invention, the electrode catalyst according to the present invention is used as the cathode catalyst contained in the cathode catalyst layer and / or as the anode catalyst contained in the anode catalyst layer, which is different from the conventional technology. Other aspects of the polymer electrolyte fuel cell (e.g., materials and structures of the electrolyte membrane, anode catalyst layer, gas diffusion layer, and separator) are not particularly limited, and the optimum ones can be selected depending on the purpose. The details of the electrode catalyst are as described above, and therefore will not be described here.
[0065] [2.2. Gas supply equipment] "Gas supply equipment" means: (a) a cathode gas supply device that supplies a cathode gas to a cathode catalyst layer; and (b) an anode gas supply device for supplying anode gas to the anode catalyst layer This refers to.
[0066] In the present invention, the gas supply device is capable of supplying unhumidified gas A or gas B adjusted to have a relative humidity of 30% RH or less to the catalyst layer containing the electrode catalyst of the present invention. That is, when the cathode catalyst layer contains the electrode catalyst of the present invention, the gas supply device is equipped with a cathode gas supply device capable of supplying unhumidified cathode gas A or cathode gas B adjusted to have a relative humidity of 30% RH or less. Alternatively or in addition, when the anode catalyst layer contains the electrode catalyst according to the present invention, the gas supply device is equipped with an anode gas supply device capable of supplying unhumidified anode gas A or anode gas B adjusted to have a relative humidity of 30% RH or less.
[0067] As described above, "supplying unhumidified gas A" means supplying gas A from a gas supply source to the fuel cell as is, without using a humidifier. In addition, "supplying gas B adjusted to have a relative humidity of 30% RH or less" means using a humidifier or condenser to adjust the relative humidity of gas A supplied from a gas supply source to 30% RH or less, and supplying the humidity-adjusted gas B to the fuel cell. It is particularly preferable that the gas supply device for supplying gas to the catalyst layer containing the electrode catalyst according to the present invention does not include a humidifier.
[0068] [4. Manufacturing method of electrode catalyst] The method for producing an electrode catalyst according to the present invention includes the steps of: a coating step of coating the surface of the catalyst particles with a coating containing polymelamine and dopamine to obtain an electrode catalyst precursor; a pyrolysis step of thermally treating the electrode catalyst precursor to pyrolyze the coating, thereby obtaining an electrode catalyst in which the surfaces of the catalyst particles are coated with a carbon film; It is equipped with:
[0069] [4.1. Covering process] First, the surface of a catalyst particle is coated with a coating containing polymelamine and polydopamine to obtain an electrode catalyst precursor (coating step). The coating step may involve coating the surface of the catalyst particles with a coating made of a mixture of polymelamine and polydopamine (simultaneous modification method). Alternatively, the coating step may include: A first coating step of coating the surface of the catalyst particles with polymelamine; a second coating step of further coating the surface of the catalyst particles with polydopamine; (sequential modification method).
[0070] [4.1.1. Catalyst particles] The catalyst particles may be supported on the surface of a carrier, or may not be supported on the surface of a carrier. Other points regarding the catalyst particles are as described above, and therefore will not be described here.
[0071] [4.1.2. Coating] The coating contains polymelamine and polydopamine. The coating may be a mixture of polymelamine and polydopamine, or may be a laminated film of polymelamine and polydopamine. In order to obtain an electrode catalyst having excellent initial activity and durability, the coating is preferably a laminated film of polymelamine and polydopamine.
[0072] When forming a coating made of a mixture of polymelamine and polydopamine, for example, dopamine hydrochloride is added to a solution in which polymelamine is dissolved, and catalyst particles (or catalyst particles supported on a carrier) are further added to this, stirred for a predetermined time, and dried. As a result, dopamine is polymerized to become polydopamine, and at the same time, the surface of the catalyst particles is coated with a coating made of a mixture of polymelamine and polydopamine (simultaneous modification method).
[0073] On the other hand, when forming a coating consisting of a laminated film, for example, first, catalyst particles (or catalyst particles supported on a carrier) are added to a solution in which polymelamine is dissolved, and the mixture is stirred for a predetermined time and dried. This results in catalyst particles coated with polymelamine. Next, the catalyst particles coated with polymelamine are added to a solution containing dopamine hydrochloride, and the mixture is stirred and dried. This causes dopamine to polymerize and become polydopamine, and at the same time, the surface of the catalyst particles coated with polymelamine is further coated with polydopamine (sequential modification method).
[0074] [4.1.3. Amount of polymelamine and polydopamine added] The amount of polymelamine and the amount of polydopamine to be added are not particularly limited, and the optimal amount can be selected depending on the purpose. By changing the amount of these, the thickness and the nitrogen content of the carbon film can be controlled.
[0075] Here, the "amount of polymelamine or polydopamine added" refers to the value represented by the following formula (1). Content (mass%)=y×100 / (y+z)…(1) however, y is the mass of polymelamine or polydopamine contained in the electrode catalyst precursor, z is the mass of the catalyst particles contained in the electrode catalyst precursor (when the catalyst particles are supported on a carrier, the total mass of the catalyst particles and the carrier)
[0076] If the amount of polymelamine added is too small, durability may decrease. Also, the amount of micropores generated may decrease, resulting in a decrease in performance. Therefore, the amount of polymelamine added is preferably 20 mass% or more. The amount of polymelamine added is more preferably 30 mass% or more, 40 mass% or more, or 50 mass% or more. On the other hand, if the amount of polymelamine added is excessive, the carbon membrane becomes too thick, and the performance may be deteriorated. Therefore, the amount of polymelamine added is preferably 95 mass% or less. The amount of polymelamine added is more preferably 90 mass% or less, or 85 mass% or less.
[0077] If the amount of polydopamine added is too small, micropores may not be formed and durability may decrease. Therefore, the amount of polydopamine added is preferably 1 mass% or more. The amount of polydopamine added is more preferably 3 mass% or more, 5 mass% or more, or 10 mass% or more. On the other hand, if the amount of polydopamine added is excessive, durability may decrease. Therefore, the amount of polydopamine added is preferably 50 mass% or less. The amount of polydopamine added is more preferably 30 mass% or less, or 25 mass% or less.
[0078] [4.2. Pyrolysis process] Next, the electrode catalyst precursor is heat-treated to pyrolyze the coating (pyrolysis step), thereby obtaining an electrode catalyst in which the surfaces of catalyst particles are coated with a carbon film. The heat treatment conditions are not particularly limited as long as the coating can be carbonized. The heat treatment is preferably performed in an inert atmosphere at a temperature of 600° C. or more and 1000° C. or less for 0.5 to 10 hours.
[0079] [5. Effect] The surfaces of the catalyst particles are coated with polymelamine and polydopamine, and the polymelamine and polydopamine are thermally decomposed to obtain an electrode catalyst in which the surfaces of the catalyst particles are coated with nitrogen and a carbon film containing micropores. When catalyst particles are covered with such a carbon film, the contact area between the catalyst particles and the ionomer is reduced. As a result, ionomer poisoning (a phenomenon in which acid groups in the ionomer are adsorbed onto the catalyst particle surface and reduce active sites) is suppressed, and catalyst activity is improved. In addition, by covering the catalyst particles with a carbon film, elution of the catalyst particles is suppressed, improving durability.
[0080] Furthermore, when the surface of the catalyst particle is covered with a nitrogen-containing carbon film, the surface of the catalyst particle becomes hydrophilic, which improves the proton conductivity on the surface of the catalyst particle and results in high power generation performance even under low humidity conditions. EXAMPLES
[0081] (Examples 1.1 to 1.5, Examples 2.1 to 2.3, Comparative Examples 1 to 2) [1. Sample preparation] [1.1. Preparation of electrode catalyst] [1.1.1. Examples 1.1 to 1.5, Examples 2.1 to 2.3] The catalyst includes: (A) Catalyst A: 30 mass% Pt / Vulcan (registered trademark) (TEC10V30E, specific surface area of carbon support: 200 m 2 / g) (Examples 1.1 to 1.5), or (B) Catalyst B: 50 mass% Pt-supported high specific surface area carbon (specific surface area of carbon support: 800 m 2 / g) (Examples 2.1 to 2.3) was used. Catalyst A was washed in advance with high-temperature (100° C.) Milli-Q (registered trademark) water (hereinafter also simply referred to as "water") and dried.
[0082] Catalyst A or Catalyst B was dispersed in a mixed solvent of water and 2-propanol, to which a polymelamine (PME) solution was added and stirred at room temperature for 3 hours. After stirring, sample powder A was collected by suction filtration and vacuum dried at 100°C for 2 hours.
[0083] Next, the dried sample powder A, dopamine hydrochloride, and Tris-HCl buffer adjusted to pH 8.5 were placed in a beaker and ultrasonically dispersed. The dispersion was then stirred for 6 hours at room temperature in the air using a stirrer. This caused dopamine to polymerize and become polydopamine (PDA).
[0084] After stirring, sample powder B was collected by suction filtration and washed with water at room temperature. Furthermore, the washed sample powder B was vacuum dried at 100°C. The obtained sample powder B was heat-treated at 700°C for 2 hours in a circular furnace while flowing Ar, and the PME and PDA were carbonized. Sample powder C after the heat treatment was washed with high-temperature (100°C) water to obtain an electrode catalyst.
[0085] The modification layer ratio of the electrode catalyst (the ratio of the mass of the carbon film to the total mass of the electrode catalyst) was adjusted by the amount of PME and PDA added. Table 1 shows the amount of PME added (= the ratio of the mass of PME to the total mass of Pt / C catalyst and PME) and the amount of polydopamine added (= the ratio of the mass of dopamine to the total mass of Pt / C catalyst and dopamine, the mass ratio of dopamine excluding hydrochloric acid) for each sample. Note that Examples 2.2 and 2.3 are electrode catalysts produced using a PME solution with a smaller amount of solvent (higher solids concentration) than Example 2.1.
[0086] [Table 1]
[0087] [1.1.2. Comparative Examples 1-2] The above catalyst A (Comparative Example 1) or catalyst B (Comparative Example 2) was subjected to only a heat treatment at 700° C. for 2 hours. The catalyst A or catalyst B after the heat treatment was subjected to various tests.
[0088] [1.2. Preparation of fuel cell] The above electrode catalyst was dispersed in a water / ethanol / Nafion (registered trademark) ionomer solution (D-2020) to prepare a catalyst ink. The water / alcohol mass ratio in the catalyst ink was approximately 1. This catalyst ink was applied onto a polytetrafluoroethylene sheet to prepare a cathode catalyst layer. The Pt weight of the cathode catalyst layer was 0.1 mg / cm. 2 The ratio of the mass of the ionomer to the mass of the carbon support (I / C) was approximately 1.
[0089] The anode catalyst layer contained 60 mass% Pt / Ketjen (registered trademark) as an electrode catalyst, Nafion (registered trademark) (D-2020) as an ionomer, and the Pt coverage was 0.2 mg / cm 2 and the I / C was 1.0.
[0090] The above-mentioned cathode catalyst layer and anode catalyst layer were thermally transferred onto both sides of a Nafion (registered trademark) membrane (NR211) to prepare a membrane electrode assembly (MEA). The thermal transfer conditions were 120° C., 50 kgf / cm 2 (4.9MPa) for 5 min. The electrode area was 1 cm 2 The MEA was sandwiched between paper diffusion layers (GDLs) with water-repellent layers to form a cell.
[0091] 2. Test Method [2.1. Mass ratio, average thickness of carbon film, and nitrogen content] The mass ratios of Pt, carrier, and carbon film (modification layer) of the obtained electrode catalyst were evaluated by thermogravimetric analysis (TG). The electrode catalysts with the highest modification layer ratios (Example 1.5 and Example 2.3) were observed with a transmission electron microscope (TEM) to evaluate the average thickness of the carbon film. Furthermore, the average thickness of the carbon film of each sample was calculated based on the modification layer ratio and average thickness. Furthermore, the nitrogen content in the electrode catalyst was quantified by a combustion method (modified Dumas method).
[0092] [2.2. Specific surface area and micropore volume] The obtained electrode catalyst was subjected to nitrogen adsorption measurement. For the nitrogen adsorption measurement, an Autosorb-iQ device manufactured by Quantachrome was used. The measurement conditions were pressure range: P / P0 = 1 × 10 -6 ~1, temperature: 77K. Next, the surface area per mass of the electrode catalyst (total specific surface area) was calculated using the BET method. The specific surface area of the micropores contained in the carbon membrane was calculated using the t-Plot method. Furthermore, the external surface area was calculated by subtracting the specific surface area of the macropores from the total specific surface area. Similarly, the volume of the micropores was calculated using the t-plot method. Furthermore, the cumulative pore volume was calculated from the pore distribution obtained by the analysis of the QSDFT method. Here, the "cumulative pore volume" refers to the cumulative value of the pore volume obtained by analyzing the entire range of data.
[0093] [2.3. Degree of hydrophilicity] The water vapor adsorption isotherm was measured for the obtained electrode catalyst. The amount of water vapor adsorbed at each relative pressure (P / P0) was calculated based on the water adsorption cross section (0.125 nm 2 ) and the surface area of the electrode catalyst, the water coverage θ H2O Furthermore, θ H2O Relative pressure (P / P0@θ H2O =0.2) was calculated and used as a measure of hydrophilicity (hereinafter also referred to as "hydrophilicity / hydrophilicity degree"). H2O The smaller the value of =0.2, the higher the hydrophilicity.
[0094] [2.4. Initial power generation performance and power generation performance after durability test] Using the obtained cell, the power generation performance after break-in (initial power generation performance) and the power generation performance after potential cycle testing (power generation performance after durability) were investigated. The power generation performance was evaluated under low humidity conditions (cell temperature: 83°C / humidification: 30% RH for both anode and cathode). The potential cycle durability test was also performed by subjecting the cell to potential fluctuations of 0.6V (held for 3s) and 1.0V (held for 3s) for 10,000 cycles.
[0095] [3. Results] [3.1. Mass ratio, average thickness of carbon film, and nitrogen content] The mass ratio, the average thickness of the carbon film, and the nitrogen content are shown in Tables 2 and 3. Whether catalyst A or catalyst B was used, the nitrogen content in the catalyst increased as the modification layer ratio increased. The reason why the modification layer ratio in Example 2.2 is larger than that in Example 2.1 is believed to be because the amount of attached PEM increased due to the use of a PEM solution with a high solids concentration.
[0096] [Table 2]
[0097] [Table 3]
[0098] [3.2. Specific surface area and micropore volume] Fig. 1 shows the total specific surface area, micropore specific surface area, and external surface area of the electrode catalysts obtained in Examples 1.1 to 1.5 and Comparative Example 1. Fig. 2 shows the total specific surface area, micropore specific surface area, and external surface area of the electrode catalysts obtained in Examples 2.1 to 2.3 and Comparative Example 2. Regardless of whether catalyst A or catalyst B was used, the electrode catalyst modified with a carbon membrane showed a tendency for the micropore specific surface area to increase as the modification layer ratio increased, indicating that micropores were formed by the carbon membrane modification.
[0099] Figure 3 shows the cumulative pore volume and micropore volume of the electrode catalysts obtained in Examples 1.1 to 1.5 and Comparative Example 1. Figure 4 shows the cumulative pore volume and micropore volume of the electrode catalysts obtained in Examples 2.1 to 2.3 and Comparative Example 2. In Figures 3 and 4, the numbers written above the bar graphs represent the cumulative pore volume, and the numbers written in the white areas within the bar graphs represent the micropore volume. Regardless of whether catalyst A or catalyst B was used, the electrode catalyst modified with a carbon membrane showed a tendency for the micropore volume to increase as the modification layer ratio increased, indicating that micropores were formed by the carbon membrane modification.
[0100] [3.3. Degree of hydrophilicity] 5 shows water vapor adsorption isotherms of the electrode catalysts obtained in Example 1.5 and Comparative Example 1. FIG 6 shows water vapor adsorption isotherms of the electrode catalysts obtained in Example 2.3 and Comparative Example 2. The water vapor adsorption amount of the carbon film-modified electrode catalyst was greater at a lower relative pressure than that of the unmodified electrode catalyst, regardless of whether catalyst A or catalyst B was used. This indicates that the nitrogen-containing carbon film modification makes the electrode catalyst hydrophilic.
[0101] Fig. 7 shows the relationship between the modification layer ratio and the hydrophilicity / hydrophobicity degree of the electrode catalyst containing catalyst A or catalyst B. In Fig. 7, the plots (●, ◯) at the position where the modification layer ratio is zero represent the hydrophilicity / hydrophobicity degrees of Comparative Example 1 and Comparative Example 2, respectively. Regardless of whether catalyst A or catalyst B is used, the higher the modification layer ratio, the greater the P / P0@θ H2O =0.2 has become smaller, and the hydrophilicity has increased.
[0102] [3.4. Initial power generation performance and power generation performance after durability test] 8 shows the IV curves at the initial stage and after the durability test of the membrane electrode assemblies obtained in Example 1.3 and Comparative Example 1. When Catalyst A was used, the initial power generation performance of Example 1.3 was higher than that of Comparative Example 1 in the range from low load to 1.0 V. The power generation performance after durability of Example 1.3 was higher than that of Comparative Example 1 in the entire range.
[0103] 9 shows the IV curves at the initial stage and after the durability test of the membrane electrode assemblies obtained in Example 2.2 and Comparative Example 2. When Catalyst B was used, the initial power generation performance and the power generation performance after the durability test of Example 2.2 both showed higher values than those of Comparative Example 2 in the entire range.
[0104] Figure 10 shows the relationship between the nitrogen content and mass activity of an electrode catalyst containing catalyst A. Figure 11 shows the relationship between the nitrogen content and mass activity of an electrode catalyst containing catalyst B. Here, "mass activity" refers to the current value per platinum mass at 0.84 V. In both catalysts A and B, the mass activity tended to increase with increasing nitrogen content. However, in the case of catalyst A, the mass activity tended to decrease when the nitrogen content was excessive. This is thought to be because the platinum utilization rate decreased or the transport resistance of the reactants increased due to the modification layer becoming too thick as the nitrogen content increased.
[0105] Figure 12 shows the relationship between the nitrogen content and mass activity retention rate of an electrode catalyst containing catalyst A. Figure 13 shows the relationship between the nitrogen content and mass activity retention rate of an electrode catalyst containing catalyst B. Here, "mass activity retention rate" refers to the ratio of mass activity after 10,000 cycles of potential fluctuation to the initial mass activity. Whether catalyst A or catalyst B was used, the mass activity retention rate tended to increase as the nitrogen content increased.
[0106] Figure 14 shows the relationship between the nitrogen content and high load performance of an electrode catalyst containing catalyst A. Figure 15 shows the relationship between the nitrogen content and high load performance of an electrode catalyst containing catalyst B. Here, "high load performance" refers to the current value at 0.6 V after correcting for cell resistance. Whether catalyst A or catalyst B was used, the higher the nitrogen content, the higher the high-load performance tended to be. However, in the case of catalyst A, when the nitrogen content was excessive, the high-load performance tended to decrease. This is thought to be because the platinum utilization rate decreased or the transport resistance of the reactants increased due to the modification layer becoming too thick as the nitrogen content increased.
[0107] Figure 16 shows the relationship between the nitrogen content and high-load performance maintenance rate of an electrode catalyst containing catalyst A. Figure 17 shows the relationship between the nitrogen content and high-load performance maintenance rate of an electrode catalyst containing catalyst B. Here, "high-load performance maintenance rate" refers to the ratio of high-load performance after 10,000 cycles of potential fluctuation to the initial high-load performance. Regardless of whether catalyst A or catalyst B was used, a tendency was observed in which the higher the nitrogen content, the higher the high load performance maintenance rate.
[0108] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]
[0109] The electrode catalyst according to the present invention can be used as a catalyst contained in a catalyst layer of a polymer electrolyte fuel cell.
Claims
1. An electrode catalyst comprising: (1) The electrode catalyst is Catalyst particles; A carbon film that covers the surface of the catalyst particle; Equipped with The carbon membrane contains nitrogen and micropores. (2) The electrode catalyst is A cathode catalyst layer of a polymer electrolyte fuel cell to which unhumidified cathode gas A or cathode gas B adjusted to have a relative humidity of 30% RH or less is supplied, and / or An anode catalyst layer of the solid polymer electrolyte fuel cell to which unhumidified anode gas A or anode gas B adjusted to have a relative humidity of 30% RH or less is supplied. It is used in.
2. 2. The electrode catalyst according to claim 1, further comprising a carbon support that supports the catalyst particles.
3. The carbon support has a specific surface area of 100 m 2 / g or more 1000m 2 The electrode catalyst according to claim 2, wherein the surface area of the electrode catalyst is 100 nm or less.
4. 2. The electrode catalyst according to claim 1, wherein the nitrogen content in the electrode catalyst is 0.1 mass % or more and 15.0 mass % or less. Here, the "nitrogen content in the electrode catalyst" refers to the ratio of the mass of nitrogen contained in the carbon film to the total mass of the electrode catalyst.
5. 2. The electrode catalyst according to claim 1, wherein the modification layer ratio is from 1.0 mass % to 50.0 mass %. Here, the "modification layer ratio" refers to the ratio of the mass of the carbon film to the total mass of the electrode catalyst.
6. 2. The electrode catalyst according to claim 1, wherein the carbon film has a thickness of 0.2 nm or more and 20 nm or less.
7. 2. The electrode catalyst according to claim 1, wherein the volume of the micropores in the carbon film is 0.001 cc / g or more and 0.3 cc / g or less.
8. The carbon membrane has a micropore specific surface area of 10 m 2 / g or more 500m 2 The electrode catalyst according to claim 1, wherein the electrocatalyst has a molecular weight of 1:1 or less.
9. The electrode catalyst according to claim 1 , wherein the catalyst particles are made of Pt or a Pt alloy.
10. A polymer electrolyte fuel cell comprising a catalyst layer containing the electrode catalyst according to claim 1; a gas supply device for supplying non-humidified gas A or gas B adjusted to have a relative humidity of 30% RH or less to the catalyst layer; A fuel cell system comprising:
Citation Information
Patent Citations
Method and apparatus for measuring fluid density
JP1989096531A
Electrode catalyst and production method thereof, and electrode for fuel cell and fuel cell
JP2020136109A
Electrode catalyst, manufacturing method thereof, electrode for fuel cell, and fuel cell
JP2022142887A